El Minecraft como recurso digital para la enseñanza y el aprendizaje de Educación Económica y Financiera en estudiantes de grado décimo de educación media (2022)
In order to reduce the margin of students who graduate from educational institutions in the country with little knowledge that can serve them to lead a healthier economic and financial life, and not fall into the desire of excessive consumption without first taking into account the purchasing power they have, this degree work aims to undertake the path of teaching Economic and Financial Education, which manages to generate greater awareness of the importance of exercising good practices with the use of money through the use of the video game Minecraf